Perceived Stress, COVID-19 Stressors, Loneliness, and Resilience of University Students after the Strictest Lockdown - Jozefiakova, Bibiana; Kascakova, Natalia; Hasto , Jozef; Tavel, Peter (Studia Psychologica, 2024)
The study explored the impact of perceived stress, stressors related to COVID-19, loneliness, and resilience on the mental health of university students after the strictest lockdown. A total sample of 2107 university students (age 18-62 years, mean age = 22.73, SD = 3.77; 63.2% of women) was recruited. Brief Resilience Scale, Brief Symptom Inventory, Perceived Stress Scale, and adapted version of the COVIDiStress survey were used. The data were analyzed using hierarchical OLS regression models. The most significant predictors of mental health indicators were perceived stress, loneliness, and resilience. However, the sum score of COVID-related stressors did not significantly increase explained variance. Specific COVID-related stressors, such as pandemic-induced loneliness, worsened relationships, and worries about infection, had notable effects on depression, anxiety, and Global Severity Index of psychopathology. The study contributes to a better understanding of the actual topic related to the COVID-19 pandemic on university students and outlines practical implications for policy making.